Marketing in the Metaverse: Unlocking Opportunities for Brands in Virtual Worlds - Adinugroho, Iwan (Pascasarjana STIE Amkop Makassar, 2024)
The rapid growth of the metaverse presents new opportunities and challenges for digital marketing. This study explores the potential of marketing within virtual worlds, examining how brands can leverage immersive technologies such as virtual reality (VR) and augmented reality (AR) to enhance user engagement and create personalized marketing experiences. Through qualitative research, including in-depth interviews with industry practitioners and platform users, the research identifies key challenges such as high development costs, technological complexity, and consumer skepticism. Despite these obstacles, the metaverse offers significant marketing potential, particularly through gamification, virtual influencers, and brand integration into digital environments. This study contributes to the development of digital marketing theories by providing a deeper understanding of virtual spaces’ impact on consumer behavior and brand interactions. Practical recommendations are made for brands seeking to enter the metaverse, emphasizing incremental approaches and consumer education. Further research is needed to assess the long-term impact of metaverse marketing on brand loyalty and consumer trust. Keywords: Metaverse, Digital Marketing, Consumer Engagement, Virtual Reality